Green Tea and Red Tea from Camellia sinensis Partially Prevented the Motor Deficits and Striatal Oxidative Damage Induced by Hemorrhagic Stroke in Rats - Priscila Marques Sosa; Mauren Assis de Souza; Pâmela B. Mello-Carpes (Neural Plasticity)
Green tea from Camellia sinensis plays a well-established neuroprotective role in several neurodegenerative diseases, including intracerebral hemorrhage (ICH). However, the other teas of the same plant do not have their properties well understood; but they can be as effective as green tea as an alternative therapy. In this study, we investigated the effects of supplementation with green tea and red tea from Camellia sinensis on motor deficits and striatum oxidative damage in rats submitted to hemorrhagic stroke (ICH). Male Wistar rats were supplemented with green tea, red tea, or vehicle for 10 days prior to ICH induction. After injury, the rats were submitted to motor tests (open field for locomotion, rotarod for balance, and neurological deficit scale (NDS)) 1, 3, and 7 days after ICH induction, while the tea supplementation was maintained. Subsequently, the rats were euthanized to striatal tissue dissection for biochemical analyzes (lipid peroxidation, reactive oxygen species, glutathione levels, and total antioxidant capacity). ICH caused locomotor and balance deficits, as well as increased the neurological deficit (NDS). Only red tea prevented locomotor deficits after injury. Green tea and red tea prevented balance deficits on the seventh day after ICH. On NDS evaluation, green tea presented a better neuroprotection than red tea (until day 3 after ICH injury). In addition, ICH increased reactive oxygen species and lipid peroxidation levels, without altering antioxidant markers. Green and red teas were effective in decreasing the lipid peroxidation levels. Therefore, green and red teas partially prevented the motor deficits and striatal oxidative damage induced by ICH. Based on our results, we can consider that the two teas seem to be equally effective to prevent motor deficits and striatal oxidative damage induced by hemorrhagic stroke in rats.